PENGARUH KINERJA KEUANGAN DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN DI INDONESIA - Gunawan, Adelia Ryanti; Lekok, Widyawati (E-Jurnal Akuntansi TSM, 2024)
The purpose of this research is to obtain empirical evidence about the effect of profitability, firm size, dividend policy, leverage, liquidity, sales growth, managerial ownership, and institutional ownership on firm value. The research objects used in this research are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for a period of 3 years, from 2021 to 2023 with 43 listed manufacturing companies used as samples in this research. The sample selection used the purposive sampling method with research data with a total of 129 data and analysis using multiple regression. The data used in this study is secondary data, consisting of financial report data and annual reports, taken from the official website of the Indonesia Stock Exchange (IDX) and the official websites of sample companies. The data analysis tool used in this research is SPSS version 25. The results of this research showed that individually, profitability, leverage, liquidity, managerial ownership, and institutional ownership have effect on firm value. Other independent variables, such as firm size, dividend policy, and sales growth have no effect on firm value.